If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + -1(5x) = 5x + 55 Remove parenthesis around (5x) 45 + -1 * 5x = 5x + 55 Multiply -1 * 5 45 + -5x = 5x + 55 Reorder the terms: 45 + -5x = 55 + 5x Solving 45 + -5x = 55 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 45 + -5x + -5x = 55 + 5x + -5x Combine like terms: -5x + -5x = -10x 45 + -10x = 55 + 5x + -5x Combine like terms: 5x + -5x = 0 45 + -10x = 55 + 0 45 + -10x = 55 Add '-45' to each side of the equation. 45 + -45 + -10x = 55 + -45 Combine like terms: 45 + -45 = 0 0 + -10x = 55 + -45 -10x = 55 + -45 Combine like terms: 55 + -45 = 10 -10x = 10 Divide each side by '-10'. x = -1 Simplifying x = -1
| 65=s-13 | | x/2+2=14 | | 3x+2+10x+8=0 | | y+32=11 | | 65=x-13 | | (2)/(x+1)+1/(2)/(x^2-x) | | -10.4x=83.2 | | x+28=32 | | -10.4=83.2 | | 7=8-4/3x | | 385=15c+85 | | 7z-z=-2+2z-3-3 | | 1.25m+30=1.75(m-100)+105 | | (.3)A=A-38.5 | | x^2-2/7x+1/49=7/49 | | x=2x+2+1 | | (x^2-9x+10)/(x-2) | | 4x=104 | | 5x*5x-13x-9+10x*1ox= | | -9+8(a-4)=8(a-5)-6 | | 16x+11=4x | | -3(h+5)+2=(h+6)-9 | | 16x+9=4x | | 16x+9=0 | | -2x=-2x-2 | | 20/1.6=x | | -2x-1=-5x+8 | | 12x+12=3(4x+6) | | 3/5x=4/5+12/5 | | 2(x+3)=3x | | 24x+12=2(12x+12) | | 15x-40y+35z= |